Perspective: Cognitive Behavioral Therapy for Insomnia Is a Promising Intervention for Mild Traumatic Brain Injury - Dietch, Jessica R.; Furst, Ansgar J. (Frontiers in Neurology, 2020)
Mild traumatic brain injury (mTBI) is a significant public health problem. Insomnia is one of the most common symptoms of TBI, occurring in 30–50% of patients with TBI, and is more frequently reported in patients with mild as opposed to moderate or severe TBI. Although insomnia may be precipitated by mTBI, it is unlikely to subside on its own without specific treatment even after symptoms of mTBI reduce or remit. Insomnia is a novel, highly modifiable treatment target in mTBI, treatment of which has the potential to make broad positive impacts on the symptoms and recovery following brain injury. Cognitive-behavioral therapy for insomnia (CBT-I) is the front-line intervention for insomnia and has demonstrated effectiveness across clinical trials; between 70 and 80% of patients with insomnia experience enduring benefit from CBT-I and about 50% experience clinical remission. Examining an existing model of the development of insomnia in the context of mTBI suggests CBT-I may be effective for insomnia initiated or exacerbated by sustaining a mTBI, but this hypothesis has yet to be tested via clinical trial. Thus, more research supporting the use of CBT-I in special populations such as mTBI is warranted. The current paper provides a background on existing evidence for using CBT-I in the context of TBI, raises key challenges, and suggests considerations for future directions including need for increased screening and assessment of sleep disorders in the context of TBI, examining efficacy of CBT-I in TBI, and exploring factors that impact dissemination and delivery of CBT-I in TBI.